5X-25=3X+11

Simple and best practice solution for 5X-25=3X+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5X-25=3X+11 equation:


Simplifying
5X + -25 = 3X + 11

Reorder the terms:
-25 + 5X = 3X + 11

Reorder the terms:
-25 + 5X = 11 + 3X

Solving
-25 + 5X = 11 + 3X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3X' to each side of the equation.
-25 + 5X + -3X = 11 + 3X + -3X

Combine like terms: 5X + -3X = 2X
-25 + 2X = 11 + 3X + -3X

Combine like terms: 3X + -3X = 0
-25 + 2X = 11 + 0
-25 + 2X = 11

Add '25' to each side of the equation.
-25 + 25 + 2X = 11 + 25

Combine like terms: -25 + 25 = 0
0 + 2X = 11 + 25
2X = 11 + 25

Combine like terms: 11 + 25 = 36
2X = 36

Divide each side by '2'.
X = 18

Simplifying
X = 18

See similar equations:

| 16(a-9)=-7-9 | | 1.4=0.2y+4 | | 3(-.72)+4y=0 | | 6X-7=71 | | 0.76=x+0.06 | | 3p-2(4-5p)=5-3p | | 1.4=0.2+4 | | 6x^2+3x=45 | | 8x^2=2x+2 | | 3x+15x=-13 | | 27x^12+36x^5+72x^3= | | X+6.3=14.7 | | 28=-6x-8 | | 2(x-4)+2*x=3(4x) | | 9=5x+4(-4x) | | 3x-8=7X+4 | | 2(5x-3+9x)-1-16x=10x-[2(x-2)-7(2x-3)] | | -11y=-99 | | x^4+x^3-18*x^2+x+1= | | -12-3= | | 5-7=12y-3-11y | | 9x-42=x+15 | | 27x^12= | | 17x=212 | | 18+7x=27+4x | | 4x-33=180 | | 9(x+8)=8x+64 | | X-7-9x=-8-2x | | 60x^11+12x^9+24x^6= | | 4x-33+x=180 | | 5x-19=73 | | 2xy+5x+6xy+3xy+(-3x)= |

Equations solver categories